2011
DOI: 10.1007/s00775-011-0769-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, DNA cleavage, and cellular effects of silibinin and a new oxovanadium(IV)/silibinin complex

Abstract: A new complex of the oxovanadium(IV) cation with the flavolignan silibinin has been synthesized and characterized. Vanadium compounds show interesting biological and pharmacological properties and some of them display antitumoral actions. Flavonoids are part of a larger group of antioxidant compounds called polyphenols which may inhibit the proliferation and growth of cancer cells. The antioxidant and antitumoral effects of silibinin and its oxovanadium(IV) complex were investigated. Silibinin acted as a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 56 publications
(73 reference statements)
0
29
0
Order By: Relevance
“…[31] Previous works, as well as preliminary studies in our laboratory show antioxidant property of silibinin. [32] Wounds are usually accompanied by pain as well as reddening and edema of the surrounding tissues. These are all classical symptoms of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Previous works, as well as preliminary studies in our laboratory show antioxidant property of silibinin. [32] Wounds are usually accompanied by pain as well as reddening and edema of the surrounding tissues. These are all classical symptoms of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, V IV O complexes formed by flavonoid ligands have been extensively studied for their potential antitumor properties; in particular, they have been demonstrated to be effective against osteosarcoma cell lines [29][30][31][32][33][34][35]. The bis-chelated V IV O species formed by quercetin and morin are very effective against the proliferation of tumoral osteoblast-like cells (UMR106) [29] and breast cancer cells (T47D and SKBR3) [33].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any adverse health effect in mice as monitored by body weight gain and diet consumption. In several studies, silibinin has been found to be non-toxic to normal or non-neoplastic cells or mice [28][29][30]23]. Overall, these findings suggest for in vivo antitumor efficacy of silibinin, although with different extent, against human pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 82%